Gagnasett: Útbreiðsla hæruburstar Campylopus introflexus (Hedw.) Brid. á Íslandi – fyrsti áfangi. ... - Wasowicz, Pawel; Vilmundardóttir, Olga Kolbrún (Náttúrufræðistofnun Íslands, 2023)
This is the data collected in 2023 during the research on the distribution of Campylopus introflexus in geothermal areas in Iceland. ...